Tuberculosis - Current Issues in Diagnosis and Management 2013
DOI: 10.5772/54630
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Evaluation of Tuberculosis

Abstract: Please use Adobe Acrobat Reader to read this book chapter for free. Just open this same document with Adobe Reader. If you do not have it, you can download it here. You can freely access the chapter at the Web Viewer here.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Mainly because these tests are far more affordable compare with the newest diagnostic tools. Despite their simplicity, these old techniques have low sensitivity and specificity rates and also very subjective and time consuming [2,3]. As shown by our previous study, one of the more advanced diagnostic technique, Multiplex PCR reverse cross blot hybridization assay has sensitivity 86.03% comparing to culture method 2,3.…”
Section: How Powerful Of Our Gold Standard Diagnostic Tools?mentioning
confidence: 93%
See 1 more Smart Citation
“…Mainly because these tests are far more affordable compare with the newest diagnostic tools. Despite their simplicity, these old techniques have low sensitivity and specificity rates and also very subjective and time consuming [2,3]. As shown by our previous study, one of the more advanced diagnostic technique, Multiplex PCR reverse cross blot hybridization assay has sensitivity 86.03% comparing to culture method 2,3.…”
Section: How Powerful Of Our Gold Standard Diagnostic Tools?mentioning
confidence: 93%
“…WHO reported that in 2012, almost half a million people worldwide developed multi-drug resistant tuberculosis (MDR-TB) and around 9.6% of those MDR-TB cases had extended drug resistant tuberculosis (XDR-TB) [1]. This surely will become an extra burden to existing tuberculosis management programs that still being hampered by difficulty in early tuberculosis identification [2,3] and highly variable vaccination efficacy [4,5]. In our opinion, the main problem of tuberculosis treatment program in many tuberculosis endemic countries is not how to treat the drug-resistant Mycobacteria in the first place but how to prevent this happened.…”
Section: Better Strategy To Prevent Drug Resistant Of Mycobacterium Tmentioning
confidence: 99%